Preemption in Capacity and Price Determination - A Study of Endogenous Timing of Decisions for Homogeneous Markets - Sandra Güth; Werner Güth (Center for Economic Studies and ifo Institute (CESifo), 2000)
Endogenous timing can help to derive the time structure of decision making instead of assuming it as exogenously given. In our study we consider a homogeneous market where, like in the model of Kreps and Scheinkman (1983), sellers determine sales capacities before prices. Sellers must serve customers, but at higher costs when demand exceeds capacitiy. Our model allows for preemption in capacity as well as in price determination. Since preemption means to decide before the random choice of cost parameters reflecting the stochastic nature of (excess) capacity costs, preemptive commitments are no obviously better timing dispositions.
Keywords: 330